Il gourmet manga al di là del sushi - Maria Teresa Orsi (Lingue Culture Mediazioni, 2017)
The imagery of many (the majority of ) Italians, especially the younger generations, seems to have abandoned the icons by longstanding tradition associated with Japanese culture, geisha and samurai, in favour of other models, which landed, in the last ten/twenty years, in the world of manga and sushi. Two terms which, along with karaoke and the less auspicious tsunami, have now become part of the Italian vocabulary. In both cases, there was also a rapid crystallisation of rooted clichés: if, on the one hand, the manga has often been assimilated only to images of violence or sentimental and exhausting platitudes, on the other, the rich and innovative landscape of Japanese cuisine has been reduced only to sushi, very often identified by the personal interpretations of other countries (the Californian rolls seem to be a case in point). Apart from stereotypes and cliché, manga and kitchen – as indeed literature and food – give rise to a happy convergence in Japan today. The article examines the role that in many manga (so-called ryōri manga) is taken by food in all its variations, from the most traditional (which does not live by sushi alone), to the one that reworks in a very felicitous way suggestions coming from other countries, from the most sophisticated that analyses any minimum dish with maniacal rigor, to the simplest and most minimalist to one that accepts fast food without much remorse. It is a complex role, which goes far beyond a limiting definition of recipes, but expands and is enriched to the point of creating stories, situations and characters that become a mirror of a particular moment in contemporary Japanese society.